Ginsenoside Rg1 can restore hematopoietic function by inhibiting Bax translocation-mediated mitochondrial apoptosis in aplastic anemia - Huiqin Cao (Nature Portfolio, 2021)
Abstract The present study investigated, the anti-apoptotic activity of Ginsenoside Rg1 (Rg1) via inhibition of Bax translocation and the subsequent recovery of hematopoietic function. Mitochondrial apoptosis in bone marrow mononuclear cells (BMNCs) was observed in aplastic anemia (AA) patients. To establish a mouse model of AA, BALB/c mice were transplanted with lymph node cells from DBA/2 donor mice via vein injection after treatment with Co60 γ-radiation. After treatment with Rg1 for 14 days, the peripheral blood and Lin–Sca-1 + c-Kit + (LSK) cell counts of the treated group were increased compared with those of the untreated model mice. In in vivo and in vitro tests of LSKs, Rg1 was found to increase mitochondrial number and the ratio of Bcl-2/Bax and to decrease damage to the mitochondrial inner and outer membranes, the mitochondrial Bax level and the protein levels of mitochondrial apoptosis-related proteins AIF and Cyt-C by decreasing the ROS level. Rg1 also improved the concentration–time curve of MAO and COX and levels of ATP, ADP and AMP in an in vitro test. In addition, high levels of Bax mitochondrial translocation could be corrected by Rg1 treatment. Levels of markers of mitochondrial apoptosis in the Rg1-treated group were significantly better than those in the AA model group, implying that Rg1 might improve hematopoietic stem cells and thereby restore hematopoietic function in AA by suppressing the mitochondrial apoptosis mediated by Bax translocation.